The effectiveness and choice of public pension scheme among Donglan county residents in China - Li Zhu; Zixuan Peng; Qucheng Deng; Xiumei Zhang (BMC Geriatrics)
Abstract Background China has made strides to achieve universal pension coverage through implementing the Public Pension Scheme for Urban and Rural Residents (PPSURR) program since 2014. This study explores the effectiveness of implementing the PPSURR in an impoverished county in China and investigates the determinants of residents’ choice on the contribution level of the PPSURR. Methodology Binary logit regression models were conducted using datasets extracted from the Chinese General Social Survey in 2021 and datasets collected through surveying 321 residents in Donglan county, China. Result The PPSURR is demonstrated to be effective in reducing coverage gap between urban and rural residents in Donglan county, indicating the feasibility to utilize administrative support and public policies (such as financial subsidies) to address the urban-rural disparity in pension coverage at the county-level. Our study also found that county residents who are rich, had higher education attainment and better understanding towards policies were more likely to participate in the PPSURR; insured residents with higher income and live in urban area were more likely to select a higher contribution level. Conclusion It’s urgent to gradually narrow benefits gap between urban and rural residents. Policy makers are suggested to offer more financial assistance for those from less wealthy backgrounds, promote public understanding towards related policies, and reduce the regional disparities.